2014
DOI: 10.15376/biores.9.4.6514-6526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Eucalyptus nitens Lignin on the Morphology and Thermo-mechanical Properties of Recycled Polystyrene

Abstract: The morphology and thermo-mechanical properties of recycled polystyrene-based materials (rPS) reinforced with 5 and 15% lignin from kraft pulping of Eucalyptus nitens were studied. The lignin was modified through two esterification processes using either acetic or maleic anhydride, and changes in the structure of the esterified lignin functional groups were analyzed by Fourier transform infrared spectroscopy. The lignin was then incorporated into rPS by melt mixing. Torque variation in the process was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…This has a direct effect on the behavior of the rubber compound [39]. Thus, the reduction of the Mooney viscosity results in good lignin miscibility, which enhances the efficiency of the processing of rubber compounds [40][41][42]. Therefore, it could increase the chain mobility and improve the flow behavior of rubber compounds.…”
Section: Mooney Viscosity and Payne Effect Of Compoundsmentioning
confidence: 99%
“…This has a direct effect on the behavior of the rubber compound [39]. Thus, the reduction of the Mooney viscosity results in good lignin miscibility, which enhances the efficiency of the processing of rubber compounds [40][41][42]. Therefore, it could increase the chain mobility and improve the flow behavior of rubber compounds.…”
Section: Mooney Viscosity and Payne Effect Of Compoundsmentioning
confidence: 99%
“…The hydroxyl groups of the lignin were reduced by the maleation and subsequently lead to a decrease in polarity as well as lower molecular interaction through hydrogen bonding. As a result, better dispersion of lignin in the PBS matrix could be attained [32].…”
Section: Surface Morphologymentioning
confidence: 99%
“…It was reported that thermal stability and flexural modulus of the composite improved when 5% esterified lignin was added to the recycled polystyrene (Pérez-Guerrero et al 2014); similar results have been reported with the addition of unmodified kraft lignin (Schorr et al 2015). However, there are no current studies that have reported on the utilization of rice straw lignin with recycled polypropylene (RPP).…”
Section: Introductionmentioning
confidence: 61%